Study of serum cortisol level in severe falciparum malaria presenting with unexplained hypotension - Pradhan, Susant; Khadanga, Sagar; Padhiary, Kashinath; Mohapatra, Biranchi Narayan; Karuna, Tadepalli; Dugar, Dharmendra (Asian Journal of Medical Sciences, 2014)
Background: Hypotension in malaria can be due to various causes. One among them is relative adrenal deficiency. World Health Organisation (WHO) and Indian malaria guidelines do not allow the use of steroid in malaria patients. But it appears prudent to use systemic steroid in those subset of malaria patients having adrenal deficiency. So the aim of the study was to prove or disprove the existence of adrenal deficiency in malaria patients. Methodology: This is a case control study which was conducted in two tertiary care centres, single blind and prospective in nature. SPSS 19 was used at the end of the study for all statistical analysis. Patient characteristics and outcome of interest is calculated with 95% confidence limits. The probability of <0.05 is considered to be significant. Results: Compared with control group the study group had significantly lower serum cortisol level at presentation (36.56±6.52 µg/dl vs. 19.43±7.29 µg/dl, p=0.006). In the study group there is significant rise in serum cortisol level after recovery from hypotension (19.96±7.29 µg/dl vs. 35.86±8.26 µg/dl, p=0.01). In control group there is slight decrease of serum cortisol level after recovery (36.85±6.42 µg/dl vs. 34.72±9.12 µg/dl, p=0.83). Conclusion: Adrenal insufficiency may be the cause of unexplained hypotension in severe falciparum malaria. Administration of systemic corticosteroid in this subset of patients seems to be justified. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11282 Asian Journal of Medical Sciences Vol.6(3) 2015 30-32